Method for forming a two-layer wet friction material having a cellulosic layer
By applying a friction coating on the outer surface of the cellulose layer of the wet friction clutch and bonding to the substrate of the fibers and filler particles to form a base layer of the wet friction material, the problem of insufficient wet strength in the existing wet friction clutch is solved, and the performance and stability of the wet friction material are significantly improved.
Patent Information
- Application Number
- CN202180013607.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-29
- Filing Date
- 2021-04-19
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-04-19
AI Technical Summary
When the friction materials in the existing wet friction clutch operate in a latent oil environment, there is a problem of insufficient wet strength, which affects its performance in motor vehicle transmissions.
By applying a friction coating on the outer surface of the cellulose layer and bonding the substrate of the fibers and filler particles to the cellulose layer, a wet friction material base layer is formed to increase the wet strength of the wet friction material.
It improves the wet strength of the wet friction material and enhances its performance stability and service life in latent oil environments.
Smart Images

Figure CN115066567B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates generally to friction clutches and plates used in torque converters and motor vehicle transmissions, and more particularly to wet friction materials. Background Art
[0002] The friction material in a wet friction clutch generally operates in an oil submerged environment and is typically a paper based material used to form a friction material ring. It is known to form the friction material by a papermaking process using a Fourdrinier papermaking machine. A double layer wet friction material is known. Summary of the invention
[0003] A method for making a wet friction material is provided. The method includes coating a first outer surface of a cellulose layer with a friction coating; placing a matrix of fibers and filler particles on a second outer surface of the cellulose layer; and impregnating the matrix of fibers and filler particles with a binder and curing the binder to bond the matrix of fibers and filler particles together to form a wet friction material base layer and bonding the wet friction material base layer to the second outer surface of the cellulose layer.
[0004] In some embodiments of the method, coating the first outer surface of the cellulose layer with a friction coating may include applying a friction solution comprising water, a solution binder, and filler particles to the first outer surface, and drying the friction solution to form a friction coating. The friction solution may include 1 wt % to 10 wt % of a solution binder, 5 wt % to 60 wt % of filler particles, and 30 wt % to 94 wt % of water. Coating the first outer surface of the cellulose layer with a friction coating may include spraying, brushing, or rolling the friction solution onto the outer surface of the cellulose layer. The friction coating may include a solution binder and filler particles. The friction coating may include 10 wt % to 30 wt % of a solution binder and 70 wt % to 90 wt % of filler particles. The friction coating may include 12.5 wt % to 25 wt % of a solution binder and 75 wt % to 87.5 wt % of filler particles. The solution binder may be nanocellulose, guar gum, or a quaternary ammonium salt. Placing a matrix of fibers and filler particles on the second outer surface of the cellulose layer may include draining a liquid in the matrix through a porous support surface on which the friction coating is placed. The method may further include compressing the substrate while the substrate is on the second outer surface of the cellulosic layer.
[0005] A method of making a component of a friction clutch is also provided, the method comprising making a wet friction material; and securing the wet friction material to a metal component of the friction clutch such that the wet friction material substrate contacts the metal component and the friction coating faces away from the metal component.
[0006] A wet friction material is also provided, comprising: a wet friction material base layer comprising a matrix of fibers and filler particles embedded in the wet friction material base layer, and a base binder; a cellulose layer including a first outer surface secured to the wet friction material base layer; and a friction coating secured to a second outer surface of the cellulose layer.
[0007] In some embodiments of the wet friction material, the friction coating may include a solution binder and filler particles. The friction coating may include 10% to 30% by weight of the solution binder and 70% to 90% by weight of the filler particles. The friction coating may include 12.5% to 25% by weight of the solution binder and 75% to 87.5% by weight of the filler particles. The fibers of the wet friction material substrate may be at least 70% by weight of aramid fibers. The filler particles may be diatomaceous earth.
[0008] A clutch assembly is also provided that includes a metal component and a wet friction material secured to the metal component such that the wet friction material substrate contacts the metal component and the friction coating faces away from the metal component. BRIEF DESCRIPTION OF THE DRAWINGS
[0009] The present disclosure is described below with reference to the following drawings, in which:
[0010] Figure 1a schematically illustrates a cellulose layer according to one embodiment;
[0011] Figure 1b A cellulose layer coated with a friction coating is schematically shown;
[0012] Figure 1c A matrix of fibers and filler particles placed on a cellulose layer is shown;
[0013] Figure 1d A wet friction material comprising a friction-coated cellulose layer and a matrix of fibers and filler particles forming a base layer is shown;
[0014] Figure 2 shows a wet friction material engaged on top of a metal part via a hot plate; and
[0015] Figure 3 Shown is wet friction material bonded to both sides of a clutch plate of a lock-up clutch assembly of a torque converter. DETAILED DESCRIPTION
[0016] The present disclosure provides a method of forming a wet friction material, the method comprising applying a friction coating to a cellulose layer, and bonding a friction material substrate to the coated cellulose layer. The cellulose layer improves the wet strength of the friction material substrate during production. The cellulose layer can be a scrim layer, i.e., a material layer used for coffee filters and tea bags.
[0017] Figures 1a to 1d A method of forming a wet friction material and a clutch assembly according to one embodiment of the present disclosure is schematically illustrated.
[0018] Figure 1a A cellulose layer 12 is shown including a flat upper outer surface 12a and a flat lower outer surface 12b. The cellulose layer 12 is formed of a thin layer of cellulose and has sufficient porosity to allow liquid to drain therethrough. The cellulose layer 12 may have a thickness of 100 to 200 microns, a viscosity of 0.05 g / cm 3 Up to 0.25g / cm 3 A density and / or a porosity of 35% to 65%.
[0019] Figure 1b A cellulose layer 12 is shown coated with a friction coating 14 on an upper outer surface 12a. The cellulose layer 12 is placed on a support surface 13, with the outer surface 12a contacting the support surface 13, which can be a movable support surface such as a conveyor, and a friction solution is applied to the cellulose layer 12 to form the friction coating 14. The friction coating 14 can be applied to the outer surface 12a by spraying, rolling or brushing. The coated cellulose layer 12 retains porosity, but the porosity is reduced after the coating 14 is applied. For example, if measured by a Gurley Precision Instruments Densometer, specifically a model 4110N Genuine Gurley Densometer, which pushes a set volume of air through the material, the time before the coating 14 is applied is 4 seconds to 9 seconds, and the time after the coating 14 is applied is 10 seconds to 20 seconds.
[0020] The friction solution may include filler particles and a binder. The binder in the solution is referred to herein as a solution binder to distinguish it from the binder added to the friction material substrate 16 described below, which is referred to herein as a substrate binder. The solution binder may be nanocellulose, such as sodium carboxymethylcellulose, guar gum, or a quaternary ammonium salt (QAS). In one embodiment, QAS is a quaternary ammonium salt having an alkyl chain containing about 16 to 18 carbon atoms. For example, QAS may be Arquad 2HT-75, which is di(hydrogenated tallow alkyl) dimethyl ammonium chloride. The filler particles may be diatomaceous earth. The friction solution may include 1% to 10% by weight of a solution binder, 5% to 60% by weight of filler particles, and 30% to 94% by weight of water. The amount of water used in the solution may depend on the application method. For example, roller coating or brush coating may require about 1 / 6 to 1 / 4 of the amount of water when spraying. For roller or brush application, the QAS-containing solution may contain 4 to 10 wt % solution binder, 10 to 60 wt % filler particles, and 30 to 86 wt % water. For spray application, the QAS-containing solution may contain 1 to 5 wt % solution binder, 5 to 30 wt % filler particles, and 65 to 98 wt % water.
[0021] After applying the QAS-containing solution to the cellulose layer 14, water is removed by drying the friction solution to finally form the friction coating 14. Drying can be performed by hot air blast drying or drying via a hot plate. In either case, the paper surface reaches a temperature of 90° C. to 110° C. After drying, the friction coating 14 may contain 10% to 30% by weight of a solution binder and 70% to 90% by weight of filler particles. In some embodiments, after drying, the friction coating 14 may contain 12.5% to 25% by weight of a solution binder and 75% to 87.5% by weight of filler particles.
[0022] like Figure 1c As shown, after the friction coating 14 is dried on the cellulose layer 12, the cellulose layer 12 is positioned on a porous support surface 16, such as a wire mesh, with the outer surface 14a of the friction coating 14 facing downward and resting on the porous support surface 16. The porous support surface 16 may be movable and may be, for example, a conveyor. A matrix 18 of fibers and filler materials bonded together in a solution is then poured on top of the outer surface 12b of the cellulose layer 12, and the remaining liquid in the matrix 18 is drained through the cellulose layer 12 and through the porous support surface 16. A material for molding the matrix 18 into a friction material substrate 22 ( Figure 1d ) mold 20.
[0023] When the substrate 18 is placed on top of the cellulose layer 12, the substrate 18 is then compressed (e.g., via rollers) to reduce the thickness of the substrate 18 and increase the density of the substrate 18. After compression, the substrate 18 is saturated with a substrate binder and then cured, such as by pressing a hot plate onto the substrate, to bond the substrate 18 to the cellulose layer 12 and form a friction material base layer 22 secured to the cellulose layer 12 to form a friction material base layer 22 such as described above. Figure 1d The wet friction material 10 shown includes a first flat outer surface 10a defined by the friction coating layer 14 and a second flat outer surface 10b defined by the friction material base layer 22. The curing of the phenolic resin solidifies and hardens the wet friction material base layer 22 to fix the fibers and particles in place, thereby improving the strength of the wet friction material 10.
[0024] Thus, the wet friction material base layer 22 is formed of fibers, filler materials, and a base binder. The fibers may be aramid fibers, organic fibers, carbon fibers, and / or glass fibers. The organic fibers may include cellulose fibers or cotton fibers. In one embodiment, at least 70% of the fibers are aramid fibers. In one embodiment, the fibers consist only of aramid fibers. The filler material may be diatomaceous earth particles. The base binder may be a phenolic resin. Optionally, a friction modifier such as graphite may also be included in the base layer 22. The fibers of the base layer 22 may have an average diameter of 45 microns to 55 microns and an average length of 1 mm to 2 mm.
[0025] In a preferred embodiment, the base layer 22 may contain 30% to 45% of fibers, 25% to 35% of filler materials, and 25% to 40% of base binder by weight. More specifically, the wet friction material 12 may contain 30% to 35% of fibers, 30% to 35% of filler materials, and 30% to 35% of base binder by weight.
[0026] like Figure 1d As shown, the wet friction material 10 is formed such that the base friction material layer 22 has a thickness T1, the cellulose layer 12 and the friction coating layer 14 together have a thickness T2, and the wet friction material 10 has a total thickness T3 between the outer surface 10a and the outer surface 10b. In a preferred embodiment, the thickness T2 of the cellulose layer 12 and the friction coating layer 14 is equal to 5% to 10% of the total thickness T3, and therefore the thickness T1 of the support layer 114 is 70% to 90% of the total thickness T3.
[0027] like Figure 2As shown, the wet friction material 10 is then placed on top of the metal component 24 so that the outer surface 10b of the wet friction material 10 contacts the flat surface 24a of the metal component 24, and the wet friction material 10 and component 24 are joined together to form a friction assembly. Due to the applied time, temperature and pressure, the adhesive film applied between the surfaces 10b and 24a creates a permanent connection between the metal component 24 and the wet friction material 10.
[0028] Figure 3 The wet friction material 10 is shown bonded to both sides of a metal component in the form of a clutch plate 40 of a locking clutch assembly 42 of a torque converter 44. The piston 46 of the locking clutch assembly 42 presses the clutch plate 40 against the inner surface 48a of the front cover 48 of the torque converter 44. The piston 46 contacts the surface 10a of the rear piece of the wet friction material 42 to press the surface 12a on the front piece of the wet friction material 10 against the inner surface 48a of the front cover 48. The piston 46 presses the clutch plate 40 against the front cover 48, thereby locking the locking clutch assembly 42 so that the torque path in the torque converter 44 to the transmission input shaft bypasses the impeller 50 and turbine 52 of the torque converter 44 and instead flows from the front cover 48 to the clutch plate 40 and through the damper assembly 54 to the transmission input shaft, which is connected to the output hub 56 of the torque converter 44.
[0029] In the foregoing description, the present disclosure has been described with reference to specific exemplary embodiments and examples thereof. However, it will be apparent that various modifications and changes may be made to the present disclosure without departing from the broader spirit and scope of the present disclosure as set forth in the appended claims. Therefore, the description and drawings should be viewed in an illustrative manner rather than in a restrictive sense.
[0030] Description of Reference Numerals
[0031] 10 Wet friction materials
[0032] 10a First flat outer surface
[0033] 10b Second flat outer surface
[0034] 12 Cellulose layer
[0035] 12a First flat outer surface
[0036] 12b Second flat outer surface
[0037] 13 Support surface
[0038] 14 Friction coating
[0039] 16 Porous support surface
[0040] 18 Matrix of fibers and filler particles
[0041] 20 Mould
[0042] 22 Wet friction material substrate
[0043] 24 Metal parts
[0044] 24a Surface
[0045] 40 Clutch plate
[0046] 42 Locking clutch assembly
[0047] 42 Locking clutch assembly
[0048] 44 Torque Converter
[0049] 46 Piston
[0050] 48 front cover
[0051] 48a Inner surface
[0052] 50 Impeller
[0053] 52 Turbine
[0054] 54 Damper assembly
[0055] 56 Output hub
[0056] 112 Double layer wet friction material
[0057] 113 Base
[0058] 114 Support layer
[0059] 114a Upper outer surface
[0060] 114b Lower outer surface
[0061] 116 Outer Layer
[0062] 116a Upper outer surface
[0063] 116b Lower outer surface
[0064] 120 Layer containing QAS
[0065] T1 Support layer thickness
[0066] T2 outer layer thickness
[0067] T3 Total thickness.
Claims
1. A method for making a wet friction material, comprising: coating a first outer surface of the cellulosic layer with a friction coating; placing a matrix of fibers and filler particles on the second outer surface of the cellulose layer, the fibers having an average diameter of 45 microns to 55 microns and an average length of 1 millimeter to 2 millimeters, and the remaining liquid in the matrix passes through the cellulose layer and drains; as well as The matrix of fibers and filler particles is impregnated with a binder and cured to bond the matrix of fibers and filler particles together to form a wet friction material base layer and to bond the wet friction material base layer to the second outer surface of the cellulosic layer.
2. The method of claim 1, wherein coating the first outer surface of the cellulose layer with the friction coating comprises applying a friction solution comprising water, a solution binder, and filler particles to the first outer surface, and drying the friction solution to form the friction coating.
3. The method of claim 2, wherein the friction solution comprises 1 to 10 wt% of a solution binder, 5 to 60 wt% of filler particles, and 30 to 94 wt% of water.
4. The method of claim 2, wherein coating the first outer surface of the cellulosic layer with the friction coating comprises spraying, brushing, or rolling the friction solution onto the first outer surface of the cellulosic layer.
5. The method of claim 1, wherein the friction coating comprises a solution binder and filler particles.
6. The method of claim 5, wherein the friction coating comprises 10 to 30 wt% of a solution binder and 70 to 90 wt% of filler particles.
7. The method of claim 5, wherein the friction coating comprises 12.5 to 25 wt% solution binder and 75 to 87.5 wt% filler particles.
8. The method according to claim 5, wherein the solution binder is nanocellulose, guar gum or quaternary ammonium salt.
9. The method of claim 1 wherein placing the matrix of fibers and filler particles on the second outer surface of the cellulosic layer comprises draining liquid in the matrix through a porous support surface upon which the friction coating rests.
10. The method of claim 1, further comprising compressing the substrate while the substrate is on the second outer surface of the cellulosic layer.
11. A method for manufacturing a component of a friction clutch, comprising: Using the method according to claim 1 to prepare a wet friction material, The wet friction material is secured to a metal component of the friction clutch such that the wet friction material substrate contacts the metal component and the friction coating faces away from the metal component.
12. A wet friction material comprising: a wet friction material base layer comprising a matrix of fibers and filler particles embedded in the wet friction material base layer, and a base binder, the fibers having an average diameter of 45 microns to 55 microns and an average length of 1 millimeter to 2 millimeters; a cellulose layer, the wet friction material base layer being fixed to a first outer surface of the cellulose layer; Also included is a friction coating secured to the second outer surface of the cellulosic layer.
13. The wet friction material of claim 12, wherein the friction coating comprises a solution binder and filler particles.
14. The wet friction material according to claim 13, wherein the friction coating comprises 10 wt% to 30 wt% of a solution binder and 70 wt% to 90 wt% of filler particles.
15. The wet friction material of claim 13, wherein the friction coating comprises 12.5 wt% to 25 wt% of a solution binder and 75 wt% to 87.5 wt% of filler particles.
16. The wet friction material of claim 12, wherein the fibers in the wet friction material base layer are at least 70% by weight aramid fibers.
17. The wet friction material of claim 12, wherein the filler particles are diatomaceous earth.
18. A clutch assembly comprising: Metal parts; and The wet friction material of claim 12, wherein the wet friction material is fixed to the metal component so that the wet friction material substrate contacts the metal component and the friction coating faces away from the metal component.
Citation Information
Patent Citations
Brake lining and process for producing same
CN103154559A
Paper friction material and method of manufacturing the same
CN107780291A
Production of friction material
JP1988309531A
Method for producing wet friction material
JP2007045860A
Friction material with high performance surface layer
US20170261057A1